ChatGPT and BCI-VR: a new integrated diagnostic and therapeutic perspective for the accurate diagnosis and personalized treatment of mild cognitive impairment - Wan Hasan, Wan Zuha; Ramli, Hafiz Rashidi; Norsahperi, Nor Mohd Haziq; Xianling, Dong (Frontiers Media SA, 2024)
The large language model, ChatGPT (OpenAI, 2024), launched by OpenAI on November 30, 2022, rapidly propelled it into the world's fastest-growing consumer software applications, attracting over a hundred million users. This milestone not only marks a significant achievement in artificial intelligence (AI) but also has sparked widespread global interest in the potential applications of AI, particularly in the medical domain (Biswas, 2023; Wójcik et al., 2023). Especially in areas such as diagnostic assistance, treatment planning and recommendations, clinical practice and guidelines, clinical research and data analysis, telemedicine, and medical resource allocation (Ferdush et al., 2023), ChatGPT has shown immense potential.